Juridical Analysis Related to the Use of Digital Evidence in Proving Violations of Debt and Receivables Agreements - Intan Fitria Ramadani; Irma Maulida; Siska Karina (International Journal of Social Service and Research, 2026)
This study aims to analyze the probative value of digital evidence in proving breaches of debt agreements and to identify the legal obstacles affecting its use. This study employs a normative legal method using both a statutory approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary sources obtained through a literature review and supported by interview findings. The results of the study indicate that digital evidence possesses probative value and can be used to prove the existence of a legal relationship, the transfer of funds, the fulfillment of obligations, or breaches of obligations in debt-credit agreements. Digital evidence, such as transfer records, account transaction histories, emails, and electronic messages, can provide relevant information in the evidentiary process. However, its use still faces various obstacles, including issues related to document authenticity, data integrity, the potential manipulation of electronic information, and limited access to certain data. Therefore, an adequate understanding of the use of digital evidence is necessary to support the effectiveness of evidence in resolving civil disputes